2017
DOI: 10.1186/s13049-017-0415-8
|View full text |Cite
|
Sign up to set email alerts
|

Serum lactate is an independent predictor of hospital mortality in critically ill patients in the emergency department: a retrospective study

Abstract: BackgroundElevated lactate has been found to be associated with a higher mortality in a diverse patient population. The aim of the study is to investigate if initial serum lactate level is independently associated with hospital mortality for critically ill patients presenting to the Emergency Department.MethodsSingle-center, retrospective study at a tertiary care hospital looking at patients who presented to the Emergency Department (ED) between 2014 and 2016. A total of 450 patients were included in the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
72
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 24 publications
13
72
3
Order By: Relevance
“…We analyzed combination scores containing qSOFA and plasma lactate measurement. As recommended in many studies, plasma lactate level is a significant predictor of mortality in seriously critical patients [12,13]. In contrast to the literature, only plasma lactate level with a cutoff value of 2 mmol/L showed a well predictive performance, but when combined with qSOFA, its efficacy of predictive value in-hospital mortality was lower in our study population.…”
Section: Discussioncontrasting
confidence: 83%
“…We analyzed combination scores containing qSOFA and plasma lactate measurement. As recommended in many studies, plasma lactate level is a significant predictor of mortality in seriously critical patients [12,13]. In contrast to the literature, only plasma lactate level with a cutoff value of 2 mmol/L showed a well predictive performance, but when combined with qSOFA, its efficacy of predictive value in-hospital mortality was lower in our study population.…”
Section: Discussioncontrasting
confidence: 83%
“…In our study, lactate levels were statistically significantly higher in nonsurvivors on the 3 rd day and at that time-point demonstrated statistically significant discriminative power regarding outcome; lactate levels higher than cut-off values were good predictors of lethal outcome with AUC of 0.64. These results are in accordance with other similar studies (29,30).…”
supporting
confidence: 94%
“…Similarly, Jansen et al [21] described that prehospital lactate �4.0 mmol/L was highly associated with in-hospital mortality, providing more prognostic information than systolic blood pressure or heart rate in 124 patients. Chebl et al [22] also reported that lactate >4.0 mmol/L in the ED was associated with an increased adjusted OR (>29.0) for in-hospital mortality. Trzeciak et al [23] reported a strong association between initial lactate � 4.0 mmol/L, wherever measured (ED, ICU, or general ward), and acute-phase death (� 3 days) in infectious patients.…”
Section: Static Lactate Indexmentioning
confidence: 95%
“…Several studies have indicated that a single initial lactate concentration in prehospital, emergency department (ED), or ICU settings is a strong predictor of outcome [20][21][22][23]. Martín-Rodríguez et al [20] demonstrated an efficient cut-off value of prehospital lactate �4.25 mmol/ L for 30-day mortality in 279 emergency patients.…”
Section: Static Lactate Indexmentioning
confidence: 99%